The unfinished business of state-owned enterprise reform in the People's Republic of China - Carsten A. Holz (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper examines the progress of state-owned enterprise (SOE) reform in the People's Republic of China. After defining SOEs and considering their scope of operation within the PRC economy, the focus of the paper is on the major reform waves that followed the deterioration of SOE profitability in the early 1990s. The oil industry serves to illustrate industry-specific SOE reform trends as well as the latest reform developments. Until today, a stable, successful, longterm arrangement of state ownership has remained elusive. SOE reform is incomplete as long as a number of fundamental governance issues are not resolved. But these are difficult to resolve in the context of Party-controlled state-owned enterprises.
Keywords: P00; P31; L20; P26; D22; L32; O25; O53; 330; state-owned enterprise reform; People's Republic of China; corporate governance; public enterprise management; Chinese Communist Party; state-owned asset management; industrial policy